2001
DOI: 10.1152/jappl.2001.91.5.2135
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oxygen uptake kinetics during concentric and eccentric cycle exercise

Abstract: O2 uptake (VO2) kinetics and electromyographic (EMG) activity from the vastus medialis, rectus femoris, biceps femoris, and medial gastrocnemius muscles were studied during constant-load concentric and eccentric cycling. Six healthy men performed transitions from baseline to high-intensity eccentric (HE) exercise and to high-intensity (HC), moderate-intensity (MC), and low-intensity (LC) concentric exercise. For HE and HC exercise, absolute work rate was equivalent. For HE and LC exercise, VO2 was equivalent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
133
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(149 citation statements)
references
References 40 publications
14
133
1
1
Order By: Relevance
“…Physiological costs of eccentric contraction are different from concentric contractions, because the recruitment pattern of eccentric exercise is different from that of an equivalent concentric workload [27]. It is reported that O 2 cost per unit of work in eccentric cycle exercise is much less than in concentric cycle exercise, but there is a similar positive relationship between O 2 cost and workload [17,19]. Bigland-Ritchie and Woods reported that the V O 2 of submaximal eccentric cycle exercise was approximately one-sixth of the same workload on a motorized bicycle ergometer at 50 rpm [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physiological costs of eccentric contraction are different from concentric contractions, because the recruitment pattern of eccentric exercise is different from that of an equivalent concentric workload [27]. It is reported that O 2 cost per unit of work in eccentric cycle exercise is much less than in concentric cycle exercise, but there is a similar positive relationship between O 2 cost and workload [17,19]. Bigland-Ritchie and Woods reported that the V O 2 of submaximal eccentric cycle exercise was approximately one-sixth of the same workload on a motorized bicycle ergometer at 50 rpm [28].…”
Section: Discussionmentioning
confidence: 99%
“…Because cycling exercise recruits a substantial muscle mass, muscle V O 2 is the primary determinant of pulmonary V O 2 [12]. Furthermore, because cycling exercise with a cycle ergometer can be coordinated at various workloads and speeds, it is widely used for V O 2 kinetics using an analysis of expired gas [12,[15][16][17][18][19]. Hooker et al determined the effects of ES cycle training for persons with spinal cord injury by evaluating V O 2 during ES cycling exercise before and after training as physiological responses [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time scale of onset differed for eccentric and concentric exercise; both showed an early rapid decline in force but a continued and slower decline with eccentric exercise. The much smaller rapid decline following eccentric contractions (ϳ30%) compared with following concentric contractions (ϳ70%) may be related to the much smaller energy use with eccentric contractions (1,33,32). If so, the time scale for the development of long-lasting fatigue (half-time 6 min) should be linked to the presence of metabolic changes following intense short-term exercise, such as inorganic phosphate (2).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the rate of thermogenesis increasing immediately at the onset of exercise, oxygen consumption increases in an exponential manner. The time constant of this response (ϳ15 to 30 s) is such that typically 1 to 3 min elapses prior to an elevated steady-state being reached (Astrand and Saltin, 1961;Hagberg et al, 1978;Ogata and Yano, 2005;Perrey et al, 2001;Whipp and Wasserman, 1972). The slight offset between the actual rate of thermogenesis and its measurement using indirect calorimetry should therefore be accounted for.…”
Section: Indirect Calorimetrymentioning
confidence: 99%